Cytogenetical analyses in three Astyanax scabripinnis populations (Pisces, Characidae) from Minas Gerais State, Brazil - Biavati, Sandra Helena; Maistro, Edson Luis [UNESP] (International Society of Cytology, 2007)
Cytogenetical data in 3 populations of characid fish assigned to the complex of Astyanax scabripinnis from São Francisco river basin and Grande river basin, Minas Gerais State, Brazil, are presented for the first time. The same diploid number, 2n=50, was detected in the 3 populations, which has conspicuous differences involving karyotype morphology: 8M, 20SM, 6ST and 16A (Cambeba stream), 6M, 28SM, 6ST and 10A (Machado headwater), 6M, 24SM, 8ST and 12A (Pedra Branca stream). Differences involving amount and/or locations of heterochromatin blocks, number and position of nucleolar organizer regions (NORs) and CMA3 positive signals were also observed. Some aspects related to the chromosome diversification of Astyanax scabripinnis are discussed. © 2007 The Japan Mendel Society.
Keywords: Astyanax scabripinnis; C-banding; Characidae; Fish cytogenetics; NOR-banding; Pisces